Carbene-catalyzed reaction of indolyl methylenemalononitriles and enals for access to complex tetrahydrocarbazoles - Mou, Chengli (2021)
A carbene-catalyzed enantioselective cascade reaction of substituted methylenemalononitriles and α-bromoenals is disclosed. Key steps of this cascade process include a formal [4 + 2] cycloaddition, aldol reaction, and intramolecular lactonization. Our reaction offers streamlined and highly stereoselective access to complex tetrahydrocarbazole derivatives, with simultaneous formation of four chemical bonds and four chiral centers.